Arreglos no convencionales en los mercados de créditos - Galarza, Francisco (2000)
The credit market is a typical one where the problem of asymmetric information exists. This raise two problems: one drawn by the impossibility to control all the borrowers' actions that could affect their capacity (insolvency default) and willingness (strategic default) to repay the loans granted, which constitutes hidden actions for lenders (moral hazard). The other problem is related to the inability of the lender to know all the credit applicant's relevant aspects in his lending decision (adverse selection or hidden information). This article focus on three non-conventional arrangements to ensure loan repayment established by formal and informal lenders to resolve the informational problem, the first established by the Cajas Municipales, the second by the NGOs, and the third is an interesting experience of vertical integration between formal (bank) and informal (NGO) lenders. All these arrangements in the credit market show that managing and sharing information about the credit applicants in the client's selection is a key instrument to ensure repayment, and may be an important substitute of the real guarantees requesting, especially in contexts where the judicial enforcement mechanisms to recover loans are very inefficient and costly, like the Peruvian case.